Protótipo para gerenciamento de equipamentos em uma emissora de televisão - Rosa, Douglas Candido (2023)
In today's business landscape, companies face complex and ever-evolving challenges driven by the need for automation and process optimization. Technology plays a pivotal role in addressing these demands by eliminating manual tasks and enhancing operational efficiency. This paper introduces an innovative project that utilizes the Raspberry Pi as an affordable and reliable solution to meet the requirements of a television broadcasting station. The proposed challenge involved the development of an application aimed at simplifying the management of audio and video processing equipment, uniting these two critical components to prevent interruptions and failures during transmission. The Raspberry Pi, due to its versatility and cost-effectiveness, emerged as the ideal choice for integrating management systems. By reducing the potential for manual errors and ensuring uninterrupted transmission, this project not only enhances program quality but also significantly reduces the operational costs of the broadcasting station. This initiative exemplifies how technology can be effectively applied to meet the growing demands of modern businesses, thereby improving operational efficiency and reliability.